Mengintegrasikan Nilai-Nilai Manajemen Islam ke dalam Tata Kelola Digital: Menuju Kerangka Kerja Global untuk Manajemen Pendidikan Berkelanjutan - Fidya Pramesti (CV SCRIPTA INTELEKTUAL MANDIRI, 2025)
This study explores the integration of Islamic managerial values into digital governance as a strategic framework for achieving sustainable educational management. Grounded in qualitative descriptive research, it investigates how principles such as amanah (trust), ‘adl (justice), shura (consultation), and itqan (excellence) can be operationalized within digital management systems of Islamic educational institutions. Data were derived from document analysis and semi-structured interviews across Indonesia, Malaysia, and Saudi Arabia, supported by official reports from the Ministry of Education and Culture (2023), UNICEF Indonesia (2021), and the International Telecommunication Union (2023). The findings reveal a substantial gap between digital readiness and ethical institutionalization, as infrastructure and human-resource competencies lag behind student adaptability. The proposed global framework interlinks value codification, technological architecture, human-capital capability, and sustainability measurement to create a cohesive, value-driven governance model. Integrating ethical and technological dimensions strengthens transparency, accountability, and institutional resilience. The study concludes that embedding Islamic managerial ethics into digital governance is essential to achieving moral coherence and long-term sustainability in global Islamic education.